Written All Over Their Faces: Neutrality and Nonverbal Expression in Sandy Hook Coverage. (September 2020) - Deavours, Danielle
During crises, it's challenging for journalists to keep their emotions out of reports. While broadcast journalists try to keep linguistic messages neutral, nonverbal behaviors are difficult to conceal. Graber's stages of crisis coverage theory discusses routines of covering crisis and preventing verbal bias but doesn't examine nonverbal bias. This study examines the neutrality of nonverbal expressions conveyed during the 2012 mass shooting at Sandy Hook Elementary School through the lens of the stages of crisis coverage theory. This study provides insight for understanding the responses news organizations should have in terms of crisis coverage. By examining the ways that the influence of emotional events have on the nonverbal expressivity of journalists during crisis, researchers can better understand the ritualization of the nonverbal neutrality standards of the profession and make recommendations on potential ways that the field could adapt their current crisis plans to consider nonverbal communication displays more explicitly. Further, by combining crisis planning, media ritualization practices, and journalistic nonverbal expression, this research provides further insight into how performance by media during a crisis can influence cultural meaning about the event for viewers. The findings in this study also suggest the stages of crisis coverage theory was not upheld by broadcasters in this context, calling for reexamination of the theory's uses and applications to all crisis coverage.